Peran Strategi Manajemen Sumber Daya Manusia dalam Mencapai Keunggulan Bersaing pada Era Kompetisi Global - Agung Utama (Efisiensi : Kajian Ilmu Administrasi, 2010)
Global competition indicated by the emerging of much competitors operate in the world market and the emerging of the competitors in other countries caused business environment becomes dynamic and tightly competition. Pursuing competitive advantage becomes the key factor on winning the competition on such environment through managing the activities of human resources based on strategic perspective. Based on this perspective, the strategy of human resource must relevance with the business strategy. Typology of human resource management strategy is an alternative approach for formulation that strategy. Identifing the needed role behavior of competitive strategy becoming the important factor on effectiveness of competitive strategy implementation.